Does online media attention improve China’s green fund performance? - Xiao, Yaping; Qiao, Haishu; Xie, Ting (Journal of Business Economics and Management, 2024)
This study investigates the relationship between online media attention and the performance of China’s green funds. The results show that increased media attention can boost the performance of green funds in the short term, however, this effect is short-lived. The mechanism of short-term positive effects may be due to increased media attention leading to larger purchases, which may undermine funds’ long-term performance. In particular, online media attention has a greater impact on larger and older funds. Moreover, it indicates that media attention reduces the returns of individual investor-dominated funds, but has little effect on institutional investor-dominated funds.